Effect of Activity Ratio, Productivity And Profitability on Liquidity in Manufacturing Companies on Indonesia Stock Exchange: Pengaruh Rasio Aktivitas, Produktivitas dan Profitabilitas terhadap Likuiditas pada Perusahaan Manufaktur di Bursa Efek Indonesia - Putri Yanti; Neni Marlina Purba (International Journal of Management and Business (IJMB), 2020)
The purpose of this study was to determine the effect of the Activity, Productivity and Profitability ratios on liquidity in Indonesian stock exchange companies. The independent variables used in this study are the ratio of activities, productivity ratios, and profitability ratios. Meanwhile, what is used as the dependent variable is the liquidity used based on the Indonesian Stock Exchange (IDX) company. The population used in this study were all manufacturing companies in the food and beverage sub-sector, totaling 17 companies. The data used is from companies that publish complete financial statement data for the 2015-2019 period. Based on the calculation results obtained t-count -2.131 <-2.03951 and the significance level is 0.041 <0.05, it is concluded that H1 is accepted, which means that there is a significant negative effect between the ratio of activity to liquidity. The productivity ratio is -0.508> -2.03951 while the significance level is 0.615> 0.05. So that the hypothesis H2 is rejected, which means that there is no influence between the productivity ratio to liquidity. Profitability ratio obtained t-value of 7.933> 2.03951 and a significance value of 0.000 <0.05, so that the hypothesis H3 is accepted, which means that there is a positive and significant effect on the ratio of profitability to the liquidity ratio and the results of data analysis obtained an f-count value of 24.014> 2.90 and a significance value. 0.000 <0.05. This shows that the activity, productivity and profitability ratios simultaneously have a significant effect on the liquidity ratio.